An anencephalic heterophagus or parasitic twin - Ahtesham Khizar; Soha Zahid; Filza Shahid; Madeha Amjad; Pradhumna Kumar Yadav (Romanian Neurosurgery, 2023)
A case of 6-week-old female twins is presented. Twin 1 was fully formed, whereas twin 2 was parasitic, adhered to the left flank, and had anencephaly and complete upper limbs. Depending on the twins' overall condition, the recommendation is to separate conjoined twins as soon as possible for a better outcome.